2020
DOI: 10.1063/5.0011585
|View full text |Cite
|
Sign up to set email alerts
|

Rotational state-changing collisions of C2H− and C2N− anions with He under interstellar and cold ion trap conditions: A computational comparison

Abstract: We present an extensive range of quantum calculations for the state-changing rotational dynamics involving two simple molecular anions which are expected to play some role in evolutionary analysis of chemical networks in the Interstellar environments, C 2 H − (X 1 Σ +) and C 2 N − (X 3 Σ −) but for which inelastic rates are only known for C 2 H −. The same systems are also of direct interest in modelling selective photo-detachment (PD) experiments in cold ion traps where the He atoms function as the chief buff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…In this case, however, the differences with the results we had found for C 5 N − at lower temperatures turn out to be smaller and therefore the two sets of de-excitation processes are very similar in size over the same range of temperatures. It is interesting at this point to also compare the inelastic rate coefficients just obtained for the long chains discussed here with those that we have calculated in the past for smaller anions with larger energy spacing between rotational states: C 2 H − and C 2 N − interacting with He atoms (Franz et al 2020) and CN − interacting with He and H 2 partners (González-Sánchez et al 2020). In the case of the former anions, in fact, our earlier calculations of the excitation rate coefficients involving the lower rotational states (Franz et al 2020) found such rates to be about one order of magnitude larger than those reported here by Figures 5 and 7.…”
Section: Inelastic Rate Coefficientsmentioning
confidence: 53%
“…In this case, however, the differences with the results we had found for C 5 N − at lower temperatures turn out to be smaller and therefore the two sets of de-excitation processes are very similar in size over the same range of temperatures. It is interesting at this point to also compare the inelastic rate coefficients just obtained for the long chains discussed here with those that we have calculated in the past for smaller anions with larger energy spacing between rotational states: C 2 H − and C 2 N − interacting with He atoms (Franz et al 2020) and CN − interacting with He and H 2 partners (González-Sánchez et al 2020). In the case of the former anions, in fact, our earlier calculations of the excitation rate coefficients involving the lower rotational states (Franz et al 2020) found such rates to be about one order of magnitude larger than those reported here by Figures 5 and 7.…”
Section: Inelastic Rate Coefficientsmentioning
confidence: 53%
“…Additionally, another small negative anion of similar size and structure, the C 2 H – , has been often surmised to be present within the same ISM environments but never really confirmed. We have already studied its collisions with He and obtained accurate estimates of its efficiency in being rotationally excited/cooled by He scattering at the same low temperatures examined in the present study . We have therefore extended the comparison between the present results and those obtained for the three systems mentioned above.…”
Section: Correct New Results and Discussionmentioning
confidence: 92%
“…As mentioned earlier, we have extended the comparison of the present calculations, which now use the correct PES to describe the interaction between the partners of the present system, to another molecular anion of similar structure, the C 2 H – negative ion, for which we had done earlier accurate calculations already reported in the literature . The results of the present comparisons are reported in the panels of Figures and .…”
Section: Correct New Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C 2 N is also well studied from a theoretical point of view [19,20] . For the C n N − anion, the cases n=1-7 ${n = 1 - 7}$ have been investigated at several levels of theory by Pascoli et al [21] and rotational state‐changing dynamics for C 2 N − have been reported by Franz et al [22] Experimentally, high resolution photoelectron spectra for C 2 N − , C 4 N − , and C 6 N − have been detected by slow electron velocity map imaging [23] . For C 2 N − the authors assigned the fundamental bending vibration.…”
Section: Introductionmentioning
confidence: 99%